Characteristics of a non-reacting spray from an outwardly opening hollow-cone injector with high-reactivity gasolines. (15th May 2020) - Du, Jianguo; Cenker, Emre; Badra, Jihad; Sim, Jaeheon; Roberts, William L.
Highlights: Spray of two high-reactivity gasoline fuels for GCI engine are experimentally characterized. Importance of fuel physical properties on fuel-air mixing are analyzed by simulation. Heat of vaporization, fuel density, surface tension and specific heat dominate penetration. Abstract: The effects of charge gas temperature, gas pressure, and fuel type on liquid penetration length and cone angle of a hollow-cone spray from an outwardly opening piezoelectric injector was investigated. High-speed diffused back-illumination extinction imaging (DBIEI) was used to perform the measurements in a constant pressure vessel. The conditions studied in this work are relevant to gasoline direct injection (GDI) and gasoline compression ignition (GCI) engine combustion: injection pressure was kept at 120 bar, in-chamber pressure and temperature were varied from 1 bar to 10 bar, and 21 °C to 200 °C, respectively. Experiments were performed with two high-reactivity gasoline fuels, namely high-reactivity gasoline 1 (HRG1) and high-reactivity gasoline 2 (HRG2), which have similar auto-ignition characteristics but substantially different distillation and physical properties. These fuels are candidates to work with future engine designs with a better performance. The motivation here was to understand what physical properties are important in air fuel mixture preparation. Liquid penetration reduces with increasing gas temperature and pressure for both fuels whereas cone angle increases only with increasing gas temperature. At high temperatures, HRG2 yields up to 25% longer liquid penetration length compared to HRG1. For a detailed understanding of effects of fuel properties on liquid penetration, a detailed numerical study was conducted using CONVERGE. By changing a single fuel property at a time, the effects of each fuel physical property was isolated. It was found that density, specific heat, surface tension and heat of vaporization are the most influential physical properties on spray penetration.